Study of chemical stability for chlorothalonil and their fungicidal effect against Fusarium solani and Botrytis cinerea. - Rasha M.A. EL-Saman; Azza R. Emara; Nahed M.M. Selim; Hala M. Ibrahim (Caspian Journal of Environmental Sciences)
This study investigated the degradation of two chlorothalonil formulations [Chlorcal 70% Wettable Powder (WP) and Open 72% Suspension Concentrate 72% (SC)]. The tested fungicides were stored at 54 ± 2°C for 14 days. During the different storage periods, samples were taken after 1, 3, 7, and 14 days to determine physical properties, evaluate the chemical stability of the active ingredient: Hexachlorobenzene as impurities by HPLC and fingerprint (GC/MS and IR), as well as the evaluation of their efficacy, by testing them against the mycelial growth of Fusarium solani and Botrytis cinerea under in vitro condition. The results indicated that Open 72% SC was the most effective fungicide against F. solani and B. cinerea it recorded the lowest EC50 value of 28.4 and 46.8 ppm respectively, followed by Chlorcal 70%WP with EC50 values of 42.9 and 59.4 ppm respectively. On the other hand, the effectiveness of tested fungicides deteriorated as the result of storage at 54 ± 2 ºC for 14 days with EC50 values increased from 28.4 to 130.9 and 46.8 to 278.1 in the case of Open 72% SC against F. solani and B. cinerea respectively, while the degradation efficiency of Chlorcal 70%WP was decreased at storage with EC50 values from 42.9 to 89.4 and 59.4 to 145.3 against these two fungi respectively. Chlorcal 70%WP was more stable at during storage and less effective against fungal pathogens and determination of chemical content (total soluble sugar; total protein; free amino acids) and some enzymes (amylase and catalase) activities of mycelium fungi. Potato dextrose (PD) media treated with chlorothalonil formulations induced a significant decrease in all components in each fungus except the catalase enzyme in the case of B. cinerea. The obtained results showed that active ingredients were 69.82%, 71.9% and reached 69.3%, and 70.75% after 14 days of storage at 54 ± 2 ºC for Chlorcal 70% WP, Open 72% SC, respectively. Also calculated half-life (T0.5) values for Chlorcal 70% WP, Open 72% SC were 1382.07 days and 614.035 days, respectively. This result refers that Chlorcal 70% WP is more stable than Open 72% SC after storage at 54 ± 2 oC for 14 days, whereas the amount of hexachlorobenzene was within the FAO limits for all sources before and after storage. Then the other tested GC / MS was used for the degradation of chlorothalonil fungicide, the two major degradation products in chlorothalonil were 2,5,6-trichloro- 4- hydroxyisophthalonitrile and 2,4,6-trichloroisophthalonitrile.